THE INTERACTION BETWEEN WATER AND ALUMINOSILICATE MAGMAS - Kohn S.C.; Dupree R.; Mortuza M.G. (My University, 1992)
29Si, 27Al and 23Na NMR data are presented for a variety of dry and dydrous aluminosilicate glasses. For 29Si and 27Al spectra only minor differences were observed between dry and hydrous glasses, but significant changes were observed in 23Na spectra. As found in our earlier study of hydrous albite glasses, the data are consistent with a model for the mechanism of water dissolution which involves no breakage of T-O-T linkages. Viscosity, phase equilibrium and vibrational spectroscopic data from other studies are discussed and shown to be consistent with such a model.